1994
DOI: 10.1063/1.467320
|View full text |Cite
|
Sign up to set email alerts
|

Free energy landscape for protein folding kinetics: Intermediates, traps, and multiple pathways in theory and lattice model simulations

Abstract: The implications of thermodynamics of heteropolymers for their folding kinetics are formulated and discussed. The predictions are tested by Monte Carlo simulation of folding of a lattice model 36-monomer proteins at different temperatures. Using a simulated annealing procedure in sequence space, a number of sequences are designed which have sufficiently low energy in a given target conformation. This conformation plays a role of the native structure for the model proteins. The folding transition is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
151
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(162 citation statements)
references
References 42 publications
9
151
2
Order By: Relevance
“…7,8,25 In fact, extensive testing for ten values of ǫ/k B T between −2.22 and −2.78 covering the quasi-linear regime and beyond indicates that they are consistent with single exponential relaxation. Unfolding kinetics is essentially single-exponential as well (detailed data not shown).…”
Section: Modeling a Cooperative Interplay Between Local Conformationamentioning
confidence: 96%
“…7,8,25 In fact, extensive testing for ten values of ǫ/k B T between −2.22 and −2.78 covering the quasi-linear regime and beyond indicates that they are consistent with single exponential relaxation. Unfolding kinetics is essentially single-exponential as well (detailed data not shown).…”
Section: Modeling a Cooperative Interplay Between Local Conformationamentioning
confidence: 96%
“…This barrier arises from the incomplete cancellation of the entropic and enthalpic contributions to folding. [3][4][5][6] Folding can proceed through a multiplicity of routes, and the transition state consists of an ensemble of structures rather than of a single conformation. Despite decades of effort, the identification of this transition state ensemble (TSE) still poses serious challenges, both experimentally and computationally.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that there is "no useful correlation between folding times and the energy gap between the native conformation and the first excited state" [1]. In response to these results Karplus and Shakhnovich (KS) [2] try to argue (i) that the folding criterion used by KT is "essentially the same as one introduced earlier [3,4]" and (ii) that the energy gap used by KT is not "appropriate". We take up these two issues separately.…”
mentioning
confidence: 99%
“…There is no plot of folding time versus T f in [3], an article that was submitted after [5] was accepted for publication. It was shown in [5] (cited in [4]) that folding times correlate with σ. We showed using numerical results and theoretical arguments that "there appears to be useful correlation between folding time τ r and σ = 1 −T f /T θ : the smaller the value of σ the smaller the value of τ r " [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation